A Study of Factors Effecting on Job Satisfaction in South Central Railway Employees - Ramesh, Vaddi.; Katta, Ashok Kumar (International Journal of Intelligent Systems and Applications in Engineering, 2022)
The level of contentment among Guntakal Railway Division workers is an intriguing topic for us. Most employees are happy with how things are going at work. The firm has a good reputation amongst the staff. The majority of employees understand the company’s direction and trust their superiors. Most workers feel they get enough recognition for their efforts. Railways that provide their employees with a living salary will be successful in the long run. As in a family, employees must help one another out and coordinate their efforts to achieve the company’s objectives. People are consistently presented with chances to showcase their skills and get praise. You can easily get in touch with the higher echelons of management.